A high speed geiger mode photodiode gating circuit modelling using matlab - Woon, Sheue Wen (2018)
Single photon avalanche diode (SPAD) is developing constantly in imaging detection area. SPAD device is very sensitive to the fabrication technique used. Different geometry, shape and size will result in devices with various current, voltage and also count rate performances. The development of new SPADs is a time and money consuming process where modelling or simulation tools will be able to help in shorten the development time and reduced the money involved. Currently, 130 nm SPAD model circuit is not available in Cadence electronic design automation (EDA) tools’ library. Therefore, there is no promising device model of SPAD that can be utilized with integrated readout circuit to predict the performance of the photon counting circuit which is developed using Cadence EDA tool. This project has been carried out to model SPAD detectors for 130 nm technology which allows researchers to simulate the behaviour of the incoming detected photon. Moreover, this project is focused on the characterisation and optimisation the mathematical SPAD model on passive quenched circuit. Hence that, the performance of the passively quenched SPAD model is investigated at low and high photon counting rate by using MATLAB Simulink. The whole project is divided into three parts which are modelling SPAD, modelling passive quenching circuit as well as compare and optimize the performance of the quenching circuit. The effect of resistance and capacitance value of SPAD model is identified. On the other hand, SPAD simulation model circuit which have been used by the previous researchers is analyzed and applied in low voltage technology. The simulation analysis on the circuit modelling is performed using spice parameters of standard 180 nm and 130 nm complementary metal-oxide semiconductor (CMOS). In conclusion, modelling SPAD will able to help researchers to understand and predict the behaviour of the SPAD and future work can be implemented by using active quenching as it enabling SPAD to operate in higher frequency. At the end of this project, a dedicated SPAD model as photon detector simulation model in low voltage CMOS process is modeled with dead time 0.21 μs which is around 4.7 MHz.